Student Responses to Video Media Tutorial Basic Physics Practicum on Series and Parallel Circuits Material - Desak Made Anggraeni; Margaretha Noni Theedens (Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This research aims to determine student responses to the development of basic physics practical video tutorial media on series and parallel circuits. This research is quantitative descriptive research. The samples used in this research were twenty-five students from the physics education study program in the odd semester of the academic year: 2022/2023 at one of the universities in Sumba who took Basic Physics courses. Data collection in this research used a questionnaire containing statements using a Likert scale. The data obtained is analyzed for each indicator in the questionnaire, then the percentage score obtained will be calculated. Based on the results of data analysis, it was found that the student response to the basic physics practical video tutorial media on series and parallel circuit material was very positive (91.3%) meaning that the use of practical video tutorial media in basic physics practicum activities on series and parallel circuit material received a response good thing from students. The percentage of each aspect measured obtained the following values: (1) the attractiveness of the practical tutorial video media was 92% (very positive category); (2) ease of use of practical video tutorial media by 94% (very positive category); and (3) the role of practical video tutorial media in series and parallel series practicum was 88% (very positive category). The results obtained show that the practical video tutorial media is highly accepted by students as a medium that can assist in basic physics practical activities, especially in series and parallel circuit material. The implication of the results of this research is that it is easier for students to understand the steps when carrying out practicum activities because there are practicum video tutorials that help students learn material related to the practicum that will be carried out, especially for practicum material regarding series and parallel circuits.